Building a Strong Image Logo Design: Human Centered Design Approach in Logo Design for SMEs in Pematang Serai Village - Yusup, Mohammad; Arpan; Ahmad, Aidil (Formosa Journal of Computer and Information Science, 2024)
This article delves into the pivotal role of Human-Centered Design (HCD) in logo development, specifically tailored for Small and Medium-sized Enterprises (SMEs) situated in Pematang Serai Village. Recognizing the essence of building a robust brand image, the study explores how HCD principles influence the entire process of logo design, from conceptualization to implementation. The exploration begins by emphasizing the iterative and user-centric nature of HCD, which ensures continuous refinement of logos based on user feedback. Visual elements are dissected for their impact on audience perception, acknowledging logos as significant visual cues influencing consumer behavior. Cultural considerations take center stage as the study draws insights from cross-national logo evaluation analysis, emphasizing the need to tailor logos to specific cultural contexts. This is particularly relevant for SMEs in Pematang Serai Village, ensuring resonance with the local community. The article concludes by offering actionable recommendations for SMEs, advocating for a continued user-centric approach, emphasis on visual appeal, cultural sensitivity, iterative refinement, and strategic logo implementation. It underscores the importance of these principles in creating logos that not only visually captivate but also emotionally connect with the target audience, thereby contributing to sustained business success